IMPLEMENTASI SISTEM PENDUKUNG KEPUTUSAN UNTUK MEMPREDIKSI KARYAWAN TELADAN MENGGUNAKAN METODE NAIVE BAYES - Wiyanto Wiyanto; Fazri Muharam Anwar (Jurnal SIGMA, 2019)
Every company always makes an assessment of its employees, but in this company it is still subjective in assessing it so that research is carried out aimed at predicting exemplary employees by implementing a decision support system to obtain objective predictions of exemplary employees with the Naive Bayes method using the absent, skill, kaizen assessment parameters teamwork and this parameter to get the criteria for exemplary employee status, good employees and poor employees. In this study using 100 training data and a test data was made with the criteria for absent value, skill, kaizen, teamwork by producing a prediction of the status of exemplary employees because it has the highest value with a value of 0.013 while for good employees 0 and poor employees is 0. Support system the decision to predict this exemplary employee using the Naive Bayes algorithm method can make it easier to obtain predictions of exemplary employees. Keywords: Decision Support System, Naive Bayes Method, Web Based